Practices of Reduction, Reusing and Recycling of Solid Wastes in the Malaysian Construction Industry - Chan, Cindy Wai Yin (2014)
3-R practices have been recognized as an important act in the construction industry as this sector is commonly acknowledged as one with a very high level of waste being generated. This study seeks to identify waste problem in the Malaysian construction field, to investigate reusable and recyclable construction waste materials on site, to identify the degree of 3-R practices in the local construction and also, to explore the advantages of 3-R practices. A literature review was conducted to collect relevant in-depth information from the research papers that have done by other researchers. Subsequently, a set of open-ended questions was formulated for interview purpose during which the opinions gathered from the interviewees had been summarized accordingly. A great number of survey questionnaire were also distributed to each of the personnel who currently work in Klang Valley or other states for their views. The survey results established that the use of durable, low maintenance materials is the most effective practice that can contribute to waste minimization and this behaviour is also most frequently practiced among the parties in the industry. Besides, insufficient environmental awareness and concern was ranked as the most significant barrier of waste minimization. It was believed that implementing 3-R practices can create an environmental beneficial to the country. In short, waste problem must be handled efficiently so as to reduce the negative impact to the environment. To realize these objectives, 3-R practices must be carried out regularly.